Single-electron transistors studied by microwave and far-infrared absorption: theoretical results and experimental proposal - Bâldea, Ioan; Köppel, Horst (Physical review. B, Condensed matter and materials physics, 2010)
We present theoretical results on microwave and far-infrared (FIR) absorption of single-electron transistors obtained within exact numerical diagonalization for finite clusters. They show that both the microwave and the FIR spectra consist of two maxima, whose origin can be understood physically. Our results on microwave absorption provide a physically intuitive qualitative interpretation of the Kondo splitting observed by Kogan [Science 304, 1293 (2004)]. The present results on the FIR absorption supplement and provide a physical insight into previous results obtained by means of the numerical renormalization group. Based on our theoretical results, we propose to conduct FIR experiments to determine the charging energy and other relevant parameters.
Gesehen am 28.11.2022